2021
DOI: 10.1155/2021/1804616
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Noise Exposure and Diabetes Risk

Abstract: Introduction. Noise is one of the most common worldwide environmental pollutants, especially in occupational fields. As a stressor, it affects not only the ear but also the entire body. Its physiological and psychological impacts have been well established in many conditions such as cardiovascular diseases. However, there is a dearth of evidence regarding diabetes risk related to noises. Aim. To evaluate the relationship between occupational exposure to noise and the risk of developing diabetes. Methods. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Eleven studies were identified that reported on the impact of noise exposure on glucose levels [Table S15] 30 45 47 51 55 56 57 60 61 72 ]; however, they could not be pooled into a meta-analysis due to differences in populations, measurement of exposures, measurement of outcome, and reporting of outcomes. Concerns with risk of bias due to confounding, exposure assessment, missing data, and measurement of outcomes were identified [Table S16].…”
Section: R Esultsmentioning
confidence: 99%
“…Eleven studies were identified that reported on the impact of noise exposure on glucose levels [Table S15] 30 45 47 51 55 56 57 60 61 72 ]; however, they could not be pooled into a meta-analysis due to differences in populations, measurement of exposures, measurement of outcome, and reporting of outcomes. Concerns with risk of bias due to confounding, exposure assessment, missing data, and measurement of outcomes were identified [Table S16].…”
Section: R Esultsmentioning
confidence: 99%
“…Exposure to harmful noise is one of the most common occupational risks, with approximately 600 million workers worldwide exposed to noise [ 16 , 17 ]. About 25% of the working population in Tunisia are exposed to high levels of noise over 85 decibels (dB) [ 6 ]. Nearly 22 million workers in the United States are also exposed to high noise levels.…”
Section: Introductionmentioning
confidence: 99%
“…Among the numerous impacts, occupational noise has a particularly prominent influence on workers' hearing and cardiovascular system [3]. Occupational noise mainly causes hearing loss of workers, especially high-frequency hearing, and it is attributed to cardiovascular diseases such as hypertension and myocardial infarction of workers [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Noise is one of the most common environmental pollutants worldwide, especially at work. As a stressor, it affects the ear and the whole body (Kacem et al, 2021).…”
Section: Introductionmentioning
confidence: 99%